Láminas biodegradables de almidón de yuca Manihot esculenta Crantz con aceite de copaiba Copaifera langsdorffii para aplicaciones alimentarias - Díaz Sangama, Emilio (2024)
The present study was carried out entirely at the LICC with cassava (Manihot esculenta C.), a piririca variety, as raw material, which to obtain the starch was processed in the pilot plant of the Faculty of Food Industries, obtaining a yield of 10%, and starch drying temperature of 40o C, then the oxidation processes were carried out, both with sodium hypochlorite and by acetylation, then it was dried at a temperature of 40°C, then it was sieved with a mesh of 100 mm, following the process the formulations were proposed: modified starch, alginate, glycerol, free copaiba oil and distilled water (0.054%, 0.0139%, 0.049%, 0.005% and 99.95% and alginate, 16 formulations followed with different percentages of inputs, when we had obtained the sheets, we proceeded to perform the mechanical tests elongation (0.2-5.4), tension test ( 0.20 -16.05), permeability of sheets (49.34-465.79) and diameter (0.19 nm), physicochemical tests: humidity (12.41-16.50), solubility (of 17.65-18.50), biodegradability (degradation time in days 11 dias) and antibacterial test. , using Escherichia coli and Streptococcus aureus bacteria, which resulted in little susceptibility to the growth of these bacteria (-).